2013
DOI: 10.1007/s00264-013-1923-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen-driven decision for implant retention in the management of infected total knee prostheses

Abstract: Purpose In prosthetic joint infections (PJIs) of the knee, debridement with implant retention is associated with a high risk of recurrence. Methods A single-centre cohort study was performed with extensive analysis of the literature covering 1980-2012. Results In 21 patients (mean age 80.4 years, 19 immunosuppressed), in association with 1.5-three months of antibiotic treatment, an attempt was made to salvage the prosthesis by open (11 patients) or arthroscopic (ten patients) debridement. After a mean follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 31 publications
4
26
2
Order By: Relevance
“…Indeed, the DAIR protocol led to an average 21 % failure rate in S. aureus-infected patients compared to a much lower failure rate with monomicrobial streptococcal infections. These findings are similar to those previously reported for infected knee prostheses where streptococci led to a lower DAIR failure risk than S. aureus [11]. These data lend support to the inclusion of the pathogen nature in clinical guidelines for DAIR decisions, in particular the presence of S. aureus (even if methicillin-susceptible) or Streptococcus spp.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Indeed, the DAIR protocol led to an average 21 % failure rate in S. aureus-infected patients compared to a much lower failure rate with monomicrobial streptococcal infections. These findings are similar to those previously reported for infected knee prostheses where streptococci led to a lower DAIR failure risk than S. aureus [11]. These data lend support to the inclusion of the pathogen nature in clinical guidelines for DAIR decisions, in particular the presence of S. aureus (even if methicillin-susceptible) or Streptococcus spp.…”
Section: Discussionsupporting
confidence: 89%
“…infections [4,6,7]. We recently reported that for DAIR-treated prosthetic total knee joint infections failure rates for S. aureus-infected patients were nearly five times higher than those due to streptococci [11]. Using a similar approach, this study reports the outcome of DAIR treatment in prosthetic hip infections due to S. aureus compared to Streptococcus spp.…”
Section: Introductionmentioning
confidence: 91%
“…The diagnosis and management of these infections are complex (3)(4)(5)(6), with outcome contingent on detection and identification of the causative microorganism(s) (6,7). The gold standard, culture of synovial fluid, periprosthetic tissue, and/or the implant itself, has been associated with a range of sensitivities (8)(9)(10)(11)(12)(13)(14) and has various turnaround times of up to 2 weeks.…”
mentioning
confidence: 99%
“…Finally, nearly all the hips in this study were infected with staphylococcus, so little can be determined regarding the effectiveness of this method of treatment for Gram-negative, mixed bacterial, or fungal infections. However, staphylococcal infections, especially those involving methicillin-resistant bacteria, are difficult to treat [28,34,59] and certainly represent a challenging test for our method.…”
Section: Discussionmentioning
confidence: 99%
“…Zurcher-Pfund et al [59] found that 33% of patients treated with débridement and retention of their implants survived without reinfection if the patients had antibiotic-sensitive bacteria, but that no patient who had either MRSA or MRSE was treated successfully. A similar study [30] reported that 96% of patients treated with débridement and implant retention had successful treatment and avoided reinfection, but that only 45% were successfully treated if the infecting organism was staphylococcus.…”
Section: Discussionmentioning
confidence: 99%